2018
DOI: 10.1155/2018/8238496
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Analysis during Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells

Abstract: Bone marrow mesenchymal stem cells (BMSCs) nowadays are regarded as promising candidates in cell-based therapy for the regeneration of damaged bone tissues that are either incurable or intractable due to the insufficiency of current therapies. Recent studies suggest that BMSCs differentiate into osteoblasts, and that this differentiation is regulated by some specific patterns of epigenetic modifications, such as DNA methylation. However, the potential role of DNA methylation modification in BMSC osteogenic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In addition to Rbpjκ, we recently identified hypomethylation in Cxcl12 gene in Dnmt3b LOF chondrocytes (20), suggesting Dnmt3b LOF could directly modify DNA methylation pattern in chondrocyte maturation-related genes. Findings from other groups also demonstrated that chondrogenic-and osteogenic-related genes could be regulated via alteration of DNA methylation in promoters (41)(42)(43). We thus speculate Dnmt3b LOF leads to progenitor differentiation defect through a combination of an altered Notch pathway and the alteration of DNA methylation in chondrogenic-and osteogenic-specific genes.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to Rbpjκ, we recently identified hypomethylation in Cxcl12 gene in Dnmt3b LOF chondrocytes (20), suggesting Dnmt3b LOF could directly modify DNA methylation pattern in chondrocyte maturation-related genes. Findings from other groups also demonstrated that chondrogenic-and osteogenic-related genes could be regulated via alteration of DNA methylation in promoters (41)(42)(43). We thus speculate Dnmt3b LOF leads to progenitor differentiation defect through a combination of an altered Notch pathway and the alteration of DNA methylation in chondrogenic-and osteogenic-specific genes.…”
Section: Discussionsupporting
confidence: 62%
“…RUNX1 involvement in DPSC osteogenesis has not been shown; nevertheless, another member of the RUNX family (RUNX2) could enhance bone deposition and facilitate novel bone formation after transplantation of RUNX2-transfected DPSCs [ 61 ]. Forkhead box protein A1/2 (FOXA1/2) has been reported as hypermethylated in the course of BMSC osteogenesis [ 62 ] and its knockdown promoted BMSC osteodifferentiation [ 63 ], which has still not been reported in DPSCs. Hypoxic conditions are known to promote cell proliferation and enhance the osteogenic differentiation of both BMSC and DPSC by inducing the expression of HIF1A (hypoxia-inducible factor 1-alpha) and upregulating the osteogenic-related genes (e.g., Oct-4, Sox2, c-Myc, RUNX2, and PPAR γ 2) [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…While much evidence has demonstrated that the osteogenic differentiation of BMSCs is intimately associated with multiple genetic factors, such as signaling molecules and growth factors, the epigenetic regulatory mechanisms underlying cell differentiation have attracted increasing attention [59,60,61]. Recent evidence has illustrated that epigenetic modifications, such as histone acetylation and DNA methylation, are involved in the cell differentiation process of BMSCs during bone regeneration [62,63]. As another layer of epigenetic regulation (RNA epigenetics), m 6 A modification has recently been reported to play important roles in cell function and the differentiation of embryonic stem cells (ESCs) and various cancer cell types [64,65,66].…”
Section: Introductionmentioning
confidence: 99%